Rainwater harvesting: a means of ensuring groundwater resources of the Barind, NW Bangladesh - Sattar, Golam Shabbir (Journal of Nepal Geological Society, 2000)
The present study focuses on rainwater harvesting for irrigation and homestead purposes. The undulatory Barind Tract (Pleistocene terrace) covers about 7,250 sq. km and is underlain by thick clay-rich palaeosol sequences. Groundwater of this region is used as the only resource to meet the increasing irrigation demand for production of food to nourish over a million people. Thick clay beds at the top of aquifer and discontinuous subsurface proximal recharge areas have significantly reduced both vertical and lateral recharge potential. Groundwater domain of the Barind Tract has also reached a critical state due to low rainfall, scarcity of surface water sources, and unplanned tapping of groundwater by ever-increasing number of tube wells. As a result, overdraft of groundwater is quite evident. The present situation apparently poses a serious threat to the ecosystem of the study area. To stop further deterioration of groundwater development in the Barind Tract, a rainwater harvesting technique was tested by excavation of ponds at on-farm level. Results of a three-year long experiment demonstrated that an appropriate and timely intervention helps the community to overcome the problem of increasingly acute water shortage. The present study revealed that the rainwater harvesting is very cost-effective and may prevent a potential economic and social disaster of the Barind Tract.